The Cult of the Folk: Ideas and Strategies after Ernest Gagnon - Smith, Gordon (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1999)
In this paper I discuss ideas of collectors (Édouard-Zotique Massicotte and Marius Barbeau) vis-à-vis the song collection of Ernest Gagnon. The Chansons populaires repertoire is viewed in different ways by Gagnon's successors as historically significant and/or insignificant, and/or an exhaustive, representative "canon" of songs. Approaches to fieldwork, transcription, and the "selection" of repertoire in these collectors' works are also studied. The second part of the paper sets up a critical frame of reference for these strategies based on current literature (e.g., Philip Bohlman, Ian MacKay). Within this discussion, Gagnon's nineteenth-century ideology of "le peuple" is considered alongside the preservationist "cult of the folk" inspiration of his successors.